2008
DOI: 10.1002/ijc.23447
|View full text |Cite
|
Sign up to set email alerts
|

Functional evidence implicating S100P in prostate cancer progression

Abstract: S100P protein regulates calcium signal transduction and mediates cytoskeletal interaction, protein phosphorylation and transcriptional control. We have previously shown how elevated S100P levels in prostate cancer strongly correlate with progression to metastatic disease. In our study, we evaluated the functional significance of S100P expression on prostate tumor growth in vitro and in vivo. S100P levels were modulated by overexpressing S100P in PC3 prostate cancer cells and by silencing S100P levels in 22Rv1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 39 publications
5
39
2
Order By: Relevance
“…The phenotypes of this cell line consist of a mixture of proliferating CTBs with a small proportion of multinucleate cell and retain most of the features of normal placental cells [22]. The in vitro data in our study showed that the proliferation of JAR cells was increased and the apoptosis rate was decreased when S100P was up-regulated, which was in accordance with previous cancer study [23,24].…”
Section: Discussionsupporting
confidence: 94%
“…The phenotypes of this cell line consist of a mixture of proliferating CTBs with a small proportion of multinucleate cell and retain most of the features of normal placental cells [22]. The in vitro data in our study showed that the proliferation of JAR cells was increased and the apoptosis rate was decreased when S100P was up-regulated, which was in accordance with previous cancer study [23,24].…”
Section: Discussionsupporting
confidence: 94%
“…The impact of CTTN suppression by HGF ligands is not easily predicted and warrants further scrutiny. Suppression of S100P expression in our dataset is not consistent with most scenarios reported in the literature including prostate cancer, where increased expression is associated with increased cell motility and cancer progression [109,110]. Although the molecular basis for these effects is not well understood and there is evidence of context dependence, interactions with ezrin, tubulin and the actin cytoskeleton affecting focal adhesions have been described [111,112].…”
Section: Metabolism and Ion Transport (Asns And Scnn1g)contrasting
confidence: 43%
“…Overexpression of S100P in PC3 cells was found to promote cell growth, proliferation and reduced basal apoptosis rate. Furthermore, prostate cancer cells overexpressing S100P are protected against camptothecin-induced apoptosis (22). In B A hepatocellular carcinoma, S100P expression downregulated by RNA interference-mediated gene silencing increased the basal levels of apoptotic cells, which suggests that S100P may act as an aggressiveness factor in HCC cells by conferring resistance to basal apoptosis (23).…”
Section: Discussionmentioning
confidence: 99%